Regulating financial derivatives : clearing and central counterparties - Balmer, Alexandra G. (Elgar financial law, 2018)
The financial crisis, which spanned 2007 and 2008, may have occurred ten years ago but the resulting regulatory implications are yet to be implemented. This book isolates the occurrences of the derivatives market, which were implied as the core accelerator and enabler of the global financial crisis. Offering a holistic approach to post-crisis derivatives regulation, this book provides insight into how new regulation has dealt with the risk that OTC derivatives pose to financial stability. It discusses the effects that post-crisis regulation has had on central counterparties and the risk associated with clearing of OTC derivatives. Alexandra G. Balmer offers a novel solution to tackle the potential negative externalities from the failure of a central counterparty and identifies potential new risks arising from post-crisis reforms. Comprehensive and astute, this book will provide legal and financial scholars, academics and lawyers with much food for thought. National supervisors and regulators will also benefit from an understanding of general market risks and factors affecting exposure to such risks.